Efecto transcripcional sobre la cicatrización de la piel de dorada (Sparus aurata L.) tras la inclusión del probiótico Shewanella putrefaciens Pdp11 en la dieta - Cerezo Ortega, Isabel M. (My University, 2021)
Due to the importance of epidermal integrity in the health of farmed fish, the effect of the probiotic Pdp11 on the skin healing process of sea bream (Sparus aurata) was studied. Thus, an RNAseq analysis has been carried out to compare the effect on wounded skin S. aurata specimens fed with control (Control_W) and probiotic diet (Probiotic_W). After 7 days inducing damage, animals that received the probiotic diet, activated genes related to the last phase of re-epithelialization, while ulcerated animals fed with control diet, activated genes related to primary healing processes.
Keywords: Peces - Enfermedades; Probiótico Pdp11